Stress-reducing effects of a brief mindfulness intervention in palliative care: Results from a randomised, crossover study - Warth, Marco; Köhler, Friederike; Aguilar-Raab, Corina; Bardenheuer, Hubert J.; Ditzen, Beate; Keßler, Jens (European journal of cancer care, 2020)
Objective Mindfulness-based interventions are a widely used and highly accepted adjunct treatment in oncology. Due to a paucity of research in advanced cancer and other terminal illnesses, we aimed to evaluate the stress-reducing effects of a brief, standardised mindfulness intervention for use in palliative care. Methods This study was a randomised, crossover trial where patients participated in both a single mindfulness intervention and a resting state control condition. The order of the conditions was randomised. Study outcomes encompassed self-report data on stress and well-being and measures of heart rate variability. All outcome data were measured at four times per day. Results Forty-two patients participated in this study. We found significantly stronger reductions in self-rated stress and mean heart rate as well as an increase in heart rate variability after the mindfulness intervention. Psychophysiological effects were strongest in the immediate pre- to post-intervention comparison, while the effect on subjective stress persisted after 20 to 40 min. No significant differences were found for self-rated well-being. Conclusions Despite the rather small magnitude of effects, the brief mindfulness intervention showed to be effective and accepted by patients in very advanced stages of a disease and could be offered by trained healthcare professionals in palliative care.
First published: 21 May 2020
Gesehen am 05.01.2022